Hakikat Pembukaan Dalam UUD 1945 - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2005)
The spirit of the 1945 constitution preamble is the fundamental principle of Indonesia. Whether or not the 1945 Constitution is changed, it relates to a political matter, so thata prohibition to change the preamble shoeldbe included In the constitution.